Investigating the Challenges Faced by Grade 8 Learners in Studying English as a Second Language, South Africa - Tiffany Marks; Sephiri David Hlohlolo (Journal of English Education and Teaching, 2026)
The study aimed to determine the challenges that Grade 8 English second-language learners face in the classroom to find possible solutions for these challenges. Both the qualitative (conducted through interviews with four Grade 8 English second-language teachers) and quantitative data (conducted through a questionnaire given to forty-seven Grade 8 English second-language learners) results indicated that Grade 8 English second-language learners struggle with many aspects of learning English, including the correct use of parts of speech, namely pronouns and tenses, sentence structure, spelling, and reading in English. The findings indicated that learners need more time to learn how to read in English, in addition to more time to master other aspects of the English language. Furthermore, classrooms should have a smaller number of learners per class to reduce the learner-teacher ratio, and all schools should have a functional library for learners to access. In compliance with both the qualitative and quantitative results, primary schools should be monitored to ensure learners are being taught relevant English content to build their English skills in preparation for high school, a teacher should be assigned a particular time each day to work exclusively on English reading to help Grade 8 English second-language learners improve this critical skill, and classrooms should make use of visual aids, such as posters and flashcards.